AN INVESTIGATION INTO THE LINGUISTIC REPRESENTATIVES OF THE THEME WAR IN ERNEST HEMINGWAY’S “FOR WHOM THE BELL TOLLS” AND BAO NINH’S “NOÃI BUOÀN CHIEÁN TRANH” (“THE SORROW OF WAR”) - Assoc. Prof. Dr TRẦN VĂN PHƯỚC (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis is an investigation into the theme War’s expressions in Hemingway’s “For Whom the Bell Tolls” and Bao Ninh’s “Nỗi Buồn Chiến Tranh” with the objective of presenting, describing and analyzing the theme War’s expressions commonly used in the two authors’ works under the linguistic representations of Semantic, Syntactic and Pragmatic features of the theme War’s expressions in the two author’s works. The thesis’ author adopted the research methodology of Qualitative and quantitative, Statistic and descriptive, Analytic ands synthetic, Comparative and contrastive, Deductive and inductive method to reach to the thesis’ aims. Within 117 data collected from Hemingway’s work and those from Bao Ninh’s work, thesis’ author give effort to discover the similarities as well as differences in linguistic representations. Last but not least, some implications for English language teaching, learning and translating would be put forward.